Acute Extremity Compartment Syndrome and the Role of Fasciotomy in Extremity War Wounds. (5th September 2018) - Gordon, Wade T; Talbot, Max; Shero, John C; Osier, Charles J; Johnson, Anthony E; Balsamo, Luke H; Stockinger, Zsolt T
Abstract: Acute compartment syndrome (CS) is a frequent and potentially devastating complication of blunt and penetrating extremity injuries. Extremity war injuries are particularly susceptible to CS due to associated vascular injuries; high Injury Severity Score; extensive bone and soft tissue injury; and frequent transportation that may limit close monitoring of the injured extremity. Treatment consists of prompt fasciotomy of all compartments in the involved segment, over their full length. Delayed or incomplete fasciotomy is associated with worse outcomes, including muscle necrosis, infection, and amputation. Enhanced pre-deployment training of surgeons decreases the need for revision fasciotomy at higher echelons of care and should be continued in future conflicts. We recommend the liberal use of prophylactic fasciotomy prior to aeromedical evacuation and after limb reperfusion. For leg fasciotomy, we recommend a two-incision approach as it is more reproducible and allows easy vascular exposure when necessary.